2009
DOI: 10.1128/jvi.00008-09
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Localization of Hepatitis Delta Virus Proteins in the Presence and Absence of Viral RNA Accumulation

Abstract: Hepatitis delta virus (HDV) encodes one protein, hepatitis delta antigen (␦Ag), a 195-amino-acid RNA binding protein essential for the accumulation of HDV RNA-directed RNA transcripts. It has been accepted that ␦Ag localizes predominantly to the nucleolus in the absence of HDV genome replication while in the presence of replication, ␦Ag facilitates HDV RNA transport to the nucleoplasm and helps redirect host RNA polymerase II (Pol II) to achieve transcription and accumulation of processed HDV RNA species. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…In this regard, Han et al observed that, in the absence of HDV RNA, HDAg accumulated in the nucleolus of transfected cells, perhaps by association with rRNA precursors (53). It remains to be determined whether such interactions occur during infection and whether they contribute to virus replication or pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Han et al observed that, in the absence of HDV RNA, HDAg accumulated in the nucleolus of transfected cells, perhaps by association with rRNA precursors (53). It remains to be determined whether such interactions occur during infection and whether they contribute to virus replication or pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, one previous report showed that the speckles are unlikely to be the major sites for HDV viral transcription or replication, as 5-bromouridine triphosphate (BrUTP) was not incorporated into viral RNA in nuclear speckles (17). In addition, a recent study concluded that the majority of HDAg in the nucleoplasm colocalizes with cellular RNAP II and is an indication of HDV RNP accumulation rather than of ongoing viral transcription (28). Although several lines of evidence indicate that the replication of HDV RNA is carried out by different cellular machineries, there still is much controversy about whether HDV genomic and antigenomic RNA replication take place in the same cellular compartment.…”
Section: Vol 84 2010 Phosphorylation-dependent Interaction Of Shdagmentioning
confidence: 99%
“…1-3). However, the different patterns observed between RPS-16::RFP and DsRedLD could be due to different properties of the two proteins: RPS-16 is a ribosomal protein whereas the hepatitis D large antigen is a viral protein which has previously been shown to localize at the nucleolus, SC-35 speckles, or the Golgi (Tan et al, 2004;Han et al, 2009). Furthermore, 3'-UTRs of these two constructs were also different in context: rsp-16::rfp was followed by its own 3'-UTR while DsRedLD was followed by the 3'-UTR of unc-54.…”
Section: Discussionmentioning
confidence: 98%